2020
DOI: 10.1108/jfc-09-2020-0191
|View full text |Cite
|
Sign up to set email alerts
|

The demographic profile of victims of investment fraud: an update

Abstract: Purpose This study aims to examine the demographic factors of investors, contributing to financial victimization that occurs in Canada from June of 2008 to December of 2019. Design/methodology/approach In all 235 cases disclosing the details of financial crime victims are collected from the Industry Regulatory Organization of Canada (IIROC) enforcement platform between June of 2009 and December of 2019 for the analysis. The study used a descriptive analysis to showcase the demographic characteristics of inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Diversity has also been reported in the association between age and fraud victims across types of fraud. Lokanan and Liu (2020) found that investors aged 60 years and above are more likely to be victims of financial frauds. Lokanan (2014) further argued that people who are retired and have limited investment knowledge are the most vulnerable to investment fraud.…”
Section: Diversity In Victims' Profiles Among the Types Of Special Financial Fraudmentioning
confidence: 99%
“…Diversity has also been reported in the association between age and fraud victims across types of fraud. Lokanan and Liu (2020) found that investors aged 60 years and above are more likely to be victims of financial frauds. Lokanan (2014) further argued that people who are retired and have limited investment knowledge are the most vulnerable to investment fraud.…”
Section: Diversity In Victims' Profiles Among the Types Of Special Financial Fraudmentioning
confidence: 99%
“…The most frequent type of offence, “unsuitable recommendations” made against the appropriate risk tolerance of the clients for profit maximization, is concerning because it involves an explicit abuse of the trust the client places in the financial adviser. Lokanan (2014) study of investor fraud in Canada found that 63% of the offenders were either relatives or friends of the victims. Having a close relationship with the adviser can be tricky because personal issues may influence professional decisions, and simple tasks such as the negotiation of fees are difficult, with family or friends expecting to pay less than regular clients.…”
Section: Resultsmentioning
confidence: 99%
“…This is when a long-term relationship with the financial advisors reduces the risk of financial exploitation and fraud (Lokanan & Liu, 2021), which again can be debatable. The role of long-term relationships with the offenders has mixed evidence of retaining (Lokanan & Liu, 2021) and invading trust (Lokanan, 2014;DeLiema, 2018). The dilution of individual factors (wealth and health) and social factors (far and near relations) feed into the confidence of the offender and encourage criminogenic tendencies.…”
Section: Financial Victimization: Need For Predictionmentioning
confidence: 99%